The Meaning of Hawa in the Qur'an Semantic Studies According to Toshihiko Izutsu - Musthofa, Abdulloh Yusuf; Nugroho, Kharis (Universitas Muhammadiyah Surakarta, 2023)
Research on 'hawa' is important to to do, because the Qur'an often mentions the word 'hawa' in a various meanings. In this case, it is often used with negative connotations. This is interesting to study using Toshihiko Izutsu's semantic analysis to get the network of meaning and the maudu'i method to get the meaning. Izutsu's semantic analysis to get the network of meaning and the maudu'i method to get the concept. Research qualitative research is the approach used. Source The source of the data comes from literature. Hawa is a necessity that cannot be denied. Hawary human being has them. Any inclination towards the delights of the world and disregard for reason and the rhawalation of Allah, is a dangerous Hawa.